Presenting a Structural Model of Resilience Based on Psychological Optimism with the Mediating Role of Cognitive Emotion Regulation Strategies in Parents of Children with Cancer - Rezaei, Soheila; Kashani Vahid, Leila; Asaseh, Maryam; Afrooz, Gholamali; Shekarchi, Babak (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: The present study aimed to present a structural model of resilience based on psychological optimism with the mediating role of cognitive emotion regulation strategies in parents of children with cancer.Methods and Materials: The research method is descriptive and correlational, utilizing structural equation modeling (SEM). The statistical population of this study included all parents of children with cancer under the care of the Mahak Institute in 2022, whose children were undergoing chemotherapy, radiotherapy, hormone therapy, and were in the treatment process. The sample size was considered to be 250 individuals, selected through convenience sampling. In the end, 236 completed and eligible questionnaires were obtained. The primary data for this study were collected using the Resilience Questionnaire (Connor & Davidson, 2003), the Life Orientation Questionnaire (Scheier & Carver, 2015), and the Emotion Regulation Questionnaire (Garnefski et al., 2001). Descriptive statistics (central indices, skewness-kurtosis) and inferential statistics, including structural equation modeling, were used to analyze the data.Findings: The results of the study, through correlation and regression tests, indicated that the structural model of the relationship between resilience and psychological optimism with the mediating role of cognitive emotion regulation strategies in parents of children with cancer fits well. Cognitive emotion regulation strategies do not mediate the relationship between resilience and psychological optimism in parents of children with cancer.Conclusion: Resilience, psychological optimism, and cognitive emotion regulation strategies, as an intertwined set, play a fundamental role in overcoming psychological and emotional disturbances in parents of children with cancer.